PENGARUH MANAJEMEN ASET TERHADAP KINERJA KEUANGAN PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Aribowo, Fajar; priyono, Hendro (PRIMA EKONOMIKA, 2022)
This study aims to analyze that influence asset management on financial performance in mining companies listed on the Indonesia Stock Exchange. Asset management includes several variables, namely, Total Asset Turnover, Fixed Asset Turnover, Inventory Turnover, Account Receivable Turnover, and Working Capital Turnover. This research uses quantitative data, the data source in this study uses secondary data from the annual mining financial reports on the Indonesia Stock Exchange for the period 2016-2018. The population in this study were all mining sector companies listed on the Indonesia Stock Exchange in 2016-2018, totaling 47 companies. The sample in this study were 14 companies. The sampling technique was using purposive sampling technique. The results of this study are (1) Total Asset Turnover has a significant effect on financial performance, namely 0.019 <0.05. Thus H1 is accepted. (2) Fixed Asset Turnover has no effect on the company's financial performance with a value of 0.178> 0.05. Thus H2 is rejected. (3) Inventory Turnover has no effect on the company's financial performance with a value of 0.086> 0.05. Thus H3 is rejected. (4) Account Receivable Turnover has no effect on the company's financial performance with a value of 0.109> 0.05. Thus H4 is rejected. (5) Working Capital Turnover has no effect on the company's financial performance with a value of 0.000> 0.05. Thus H5 is rejected.